Investigating the association between rs361525 promotor polymorphism with risk of multiple sclerosis: a meta-analysis - H. R. Vinoda Kumar; V. Shree Harsha; Kshama Nadig; C. Reddy Prasad; T. Thirunavvkkarasu (Egyptian Journal of Medical Human Genetics)
Abstract Background Multiple sclerosis is an autoimmune condition that affects the spinal cord and brain which is categorized by demyelination, swelling, and axonal loss. The meta-analysis rationale was to determine the correlation between TNFα gene polymorphism and multiple sclerosis risk. Methods We conducted a systematic literature mining in the major electronic databases, including PubMed, Embase, Medline Scopus, and to look up for relevant studies published up to December 2024. We executed the meta-analysis to assess the correlation between TNFα gene (rs361525) SNP and multiple sclerosis. This meta-analysis was executed using the MetaGenyo and RevMan V-5.0 software to estimate the odds ratio along with 95% confidence interval. Results Our results indicated a positive association of TNFα with OR = 1.03, (95% CI [0.530–1.980]), p = 0.04 in the dominant genetic model. These findings support the evidence that TNFα rs361525 polymorphism was found to be linked with MS risk. However, case–control studies with large sample size from Caucasian and Asian ethnicity are required to investigate the functional role of TNFα polymorphism in the multiple sclerosis pathogenesis.